تطبيق طريقة تقديم القصة لترقية مهارة الكلام في مركز ترقية اللغة الأجنبية بمعهد النور الجديد الإسلامي بيطان بربولنجو - Fitria - Cinta (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2022)
This study aims to determine the application of storytelling to improve speaking skills at the  Foreign Language Development Institute at the Nurul Jadid Islamic Boarding School Paiton Probolinggo. The research method used is descriptive qualitative research. Data collection tools are observation, interviews and documentation. The implementation steps are as follows: determining the presenter to be included in the schedule, writing the story text, memorizing the story, practicing, making up presenter, presenting the story, and having evaluation from supervisor. The driving factors in applying the taqdimul qissoh method to improve speaking skills are the strong determination of the students in learning Arabic (especially speaking skills), the activities that encourage the improvement of speaking skills, the punishment for those who cannot speak Arabic, the language environment, and the professionalism of the teacher. As for the inhibiting factors, students lack confidence and not memorizing the text of the story.